Rekayasa Sistem Pelayanan Mandiri Perpustakaan Berbasis Komputer Studi Kasus : Perpustakaan Universitas Riau - Yasin Setiawan; Evi Susanti (Perpustakaan Universitas Riau, 2013)
Library services is one of the pillars of the library activities. Among the main activities in the field oflibrary services is a service of the circulation. Circulation services is a common activity in whichlibrary services consist of sub-activities of borrowing and returning library materials, especiallyprinted books. The development of technology has influenced the way circulation services, which areinitially using the manual method, switching to the automated method, which is based administrationsystems or computer technology known as the library automation system. By using the automatedattendant system equipped computer tools to carry out services. Technological developments did notstop there, the service-based automation system is being developed for the better. One is thedevelopment of self-service infrastructure, where library user directly served by the machine. Theresearch outlined in this paper is the development of self-service engineering research. This studyincludes the analysis and design of computer-based self-service systems, which consist of members ofthe library system checks automatically, independent book-lending system and the system returns astandalone book. The technology used is a web-based system, by maximizing the use of technologyLAMP (Linux, Apache, Mysql and PHP). The results of this study generates a computer-based selfservicetools that will be applied in Riau University Library.